O KONTROWERSJACH PRACOWNICZEGO ZATRUDNIENIA CZŁONKÓW ZARZĄDU SPÓŁDZIELNI - Redakcja (Wydział Prawa i Administracji UAM, 2004)
For some time the legal grounds for employment of board members of a cooperative have been causing much controversy in the cooperative practice and jurisdiction. In accordance with article 52 of the Cooperative Law such grounds can be provided by an contract of employment or an act of appointment. The provisions of article 68 of the Labour Code, which were changed in 1996, allow employment on the basis of appointment in cases stipulated in special provisions. The resolution of a panel of 7 Supreme Court judges of February 2003 attempts to explain and solve some significant discrepancies in the appraisal of this legal status. However, the thesis of this resolution and its justification raise some numerous doubts. The aim of this study is to present these doubts and to show a fundamentally opposite standpoint. In addition to the aforementioned main subject of discussion, the following problems have been brought up: a ban on competition imposed on the board members, the influence of violating this ban on keeping the mandate by the board members and their employment with the cooperative. The study is also interested in the problem of possible responsibility for keeping order by board members, especially in the context of relationship between the board and the supervisory board. The study suggests in the conclusion that the new cooperative law should contain means which would minimize or eliminate the aforementioned controversies.
CONTROVERSIES OVER EMPLOYMENT OF BOARD MEMBERS OF COOPERATIVES